The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/anie.201912338
|View full text |Cite
|
Sign up to set email alerts
|

Single Electron Transfer to Diazomethane–Borane Adducts Prompts C−H Bond Activations

Abstract: While (Ph2CN2)B(C6F5)3 is unstable, single electron transfer from Cp*2Co affords the isolation of stable products [Cp*2Co][Ph2CNNHB(C6F5)3] 1 and [Cp*Co(C5Me4CH2B(C6F5)3)] 2. The analogous combination of Ph2CN2 and BPh3 showed no evidence of adduct formation and yet single electron transfer from Cp*2Cr affords the species [Cp*2Cr][PhC(C6H4)NNBPh3] 3 and [Cp*2Cr][Ph2CNNHBPh3] 4. Computations showed both reactions proceed via transient radical anions of the diphenyldiazomethane–borane adducts to effect C−H bond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 86 publications
0
18
0
Order By: Relevance
“…In probing related main group chemistry, in 2012, we explored reactions of boranes with diazomethanes, demonstrating carbene insertion into B−C bonds (Scheme 1). [8] However, in 2017, we isolated the unstable Ph 2 CN 2 B(C 6 F 5 ) 3 [9] which was subsequently stabilized by single electron reduction, leading to radical‐based intra‐ or intermolecular C−H bond activation [10] . In parallel studies, we and others also showed that diazoesters [11] and diazonium cations [12] reacted with phosphine donors, affording adducts of the form EtOC(=O)CHNN(PR 3 ), [ArN(PPh 3 )N(PPh 3 )] + and [ArN 2 (PR 3 )] + , respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In probing related main group chemistry, in 2012, we explored reactions of boranes with diazomethanes, demonstrating carbene insertion into B−C bonds (Scheme 1). [8] However, in 2017, we isolated the unstable Ph 2 CN 2 B(C 6 F 5 ) 3 [9] which was subsequently stabilized by single electron reduction, leading to radical‐based intra‐ or intermolecular C−H bond activation [10] . In parallel studies, we and others also showed that diazoesters [11] and diazonium cations [12] reacted with phosphine donors, affording adducts of the form EtOC(=O)CHNN(PR 3 ), [ArN(PPh 3 )N(PPh 3 )] + and [ArN 2 (PR 3 )] + , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…[8] However, in 2017, we isolated the unstable Ph 2 CN 2 B-(C 6 F 5 ) 3 [9] which was subsequently stabilized by single electron reduction, leading to radical-based intra-or intermolecular CÀ H bond activation. [10] In parallel studies, we and others also showed that diazoesters [11] and diazonium cations [12] reacted with phosphine donors, affording adducts of the form EtOC(=O)CHNN(PR 3 ), [ArN(PPh 3 )N(PPh 3 )] + and [ArN 2 (PR 3 )] + , respectively. Subsequently, related chemistry of boranes and diazoesters has been exploited in organic synthesis by Melen and co-workers.…”
mentioning
confidence: 85%
“…Nonetheless, this received little attention, as interactions of main group species with N 2 were all but unknown . Our initial efforts in that general direction involved reactions of the bulky diazomethane adduct of B­(C 6 F 5 ) 3 , and their subsequent one-electron reduction chemistry . While these species provided an N 2 fragment between B and the carbene-like fragment, they could not be generated from N 2 (Figure ).…”
Section: Small Molecule Substratesmentioning
confidence: 99%
“…80 Our initial efforts in that general direction involved reactions of the bulky diazomethane adduct of B(C 6 F 5 ) 3 , 81 and their subsequent one-electron reduction chemistry. 82 While these species provided an N 2 fragment between B and the carbene-like fragment, they could not be generated from N 2 (Figure 1). However, the landmark report of N 2 fixation by a boron(I) species reported by Braunschweig et al 83 supported the view that B(III) plus two electrons (i.e., an FLP) could also mimic this reactivity, although this has not been realized to date.…”
Section: ■ Small Molecule Substratesmentioning
confidence: 99%
“…172 They next explored the possibility of stabilizing the weak B•••N interaction of diazomethane-borane adducts by single electron transfer (SET) (Scheme 24). 173 The adduct between diphenyldiazomethane (79) and B(C6F5)3 ( 41) was reacted at -35 °C with one equivalent of decamethylcobaltocene to readily give two new compounds (82) and ( 83) containing a tetracoordinated boron atom according to 11 B NMR. The 1 H NMR spectrum also revealed the formation of an N-H bond and the presence of a CH2 fragment.…”
Section: Condensed Phase Models Using Diazo Compoundsmentioning
confidence: 99%